Nitrogen-doped carbon dots from empty fruit bunch carboxymethylcellulose for selective detection of copper ions in aqueous media - Issa Al-Badri, Mohammed Abdullah (2019)
Fluorescent carbon dots (CDs) have emerged as sensing systems for wastewater treatment and chemical sensing. Nowadays, different biomass-based materials, including the usage of starch, glucose, and cellulose have been widely employed for the production of CDs. In spite of their sustainability, the fluorescent efficiency of the obtained CDs from these natural resources is still low. This motivates the researchers for doping CDs with various heteroatom species such as nitrogen doping agent. However, long-time synthesis process from 7-72 hr is normally required for obtaining a relatively low fluorescence quantum yield (QY). Additionally, a clear formation mechanism for nitrogen-doped CDs (N-CDs) synthesized hydrothermally from biomass and various heteroatom doping sources along with the origin of the photoluminescence (PL) emission are still under debate.